Impact of impurities on the effective charge state distribution in the limiter plasmas of Wendelstein 7-X. (January 2019) - Cosfeld, J.; Rack, M.; Reiter, D.; Drews, P.; Feng, Y.; Zhang, D.
Highlights: We studied the influence of suspected main plasma impurities like carbon and oxygen on plasma parameters such as n e and Z eff profiles The effective charge state distribution was identified as an essential input for the data processing step of Langmuir probes installed on W7-X This is now further underlined by quantifying the influence of the next candidate impurity (oxygen) on Z eff . Plausible oxygen release rates as obtained from parameter scans must indeed be considered as significant, at least judging on the basis of the present status of the impurity transport model. Abstract: Carbon and oxygen have been identified as the two major impurities in the first limiter operational phase of the stellarator Wendelstein 7-X. We evaluate basic differences between these impurities regarding the effective charge state in the boundary region of the plasma utilizing a computational approach. The method applied here is based on the previous work [1] and extends it to two different impurity components within the same simulation. EMC3-EIRENE [2, 3] is applied here as a three dimensional edge plasma interpretation tool. Simulations indicate that an about twice as high release rate of carbon atoms is required to radiate the same amount of power as a pure (atomic) oxygen impurity, under the considered plasma parameters. A parameter scan of relative carbon to oxygen radiation contributions allows the corresponding impurity release fraction to be quantified, if one of the two release rates is known. Assuming the typical empirical carbon release rate of 2% of the incident hydrogen ion flux, we find that then there must be a significant additional oxygen source in the system in order to match the measured power loss.